Gold–clay nanocomposite colloids with liquid-crystalline and plasmonic properties. Issue 80 (17th September 2021) - El Rifaii, Karin; Davidson, Patrick; Michot, Laurent; Hamon, Cyrille
Abstract : Beidellite clay liquid-crystal (LC) suspensions are colourless because the distance between nanosheets is too small. We achieved a successful marriage between this colloidal host and gold nanoparticles, imparting the LC with the vivid colors of gold. Abstract : Imparting liquid-crystal (LC) materials with the plasmonic properties of metal nanoparticles is actively pursued for applications. We achieved this goal by synthetizing gold nanoparticles onto clay nanosheets, leading to nematic nanocomposite suspensions. Optical observations and structural analysis show the growth of the gold nanoparticles without altering the LC properties of the nanosheets. These colloids display plasmonic structural colours and they can be aligned by an electric field, which is relevant for fundamental and materials chemistry of colloidal LC.